Exploring the Complex Interplay: Fatty Liver Severity, Epicardial Fat Volume, and Coronary Artery Calcification - Seyed Kamaledin Hadei; Eghbal Abarvazn (پزشکی بالینی ابن سینا, 2024)
Background and Objective: Cardiovascular diseases and nonalcoholic fatty liver disease are the most common non-communicable diseases in most developed countries, and due to lifestyle changes, their incidence is increasing day by day. The present study aimed to assess the correlation of fatty liver with epicardial fat volume and coronary artery calcium score. Materials and Methods: This cross-sectional study was conducted on 136 patients referred to Hamadan Farshchian Cardiovascular Hospital for computed tomography (CT) angiography. They were selected using a consecutive sampling method. Using a 128-slice multidetector CT scanner, the coronary artery calcium score based on the Agatston criteria and epicardial fat volume were measured. A liver ultrasound was performed using a GE voluson E6 and a 3-5 MHz depth probe, and the severity of the fatty liver was determined based on the echogenicity of the liver on the ultrasound. Data analysis was conducted using the SPSS software (version 26). Results: The mean age scores of patients were 52.90±12.10 years. Regarding gender, 50.5% and 49.5% of cases were male and female, respectively. In terms of fatty liver grade, 64 (47.1%), 48 (35.3%), 21 (15.4%), and 3 (2.2%) cases had grades zero, I, II, and III, respectively. The mean calcium score was 30.76±35.40, and epicardial fat volume was 86.84±36.56. The severity of fatty liver demonstrated no significant relationship with calcium score and epicardial fat (P>0.05). Conclusion: As evidenced by the obtained results, the severity of fatty liver had no relationship with the amount of coronary epicardial fat and coronary artery calcium.